Is Morphological Awareness a Relevant Predictor of Reading Fluency and Comprehension? New Evidence From Italian Monolingual and Arabic-Italian Bilingual Children - Vernice, Mirta; Pagliarini, Elena (Frontiers in Communication, 2018)
In the current study we examined the contribution of morphological awareness to reading competence in a group of Italian L1 and Arabic-Italian early L2 children, i.e., exposed to Italian before 3 years of age. Children from first to fifth grade (age range: 6 to 11 years old) were tested on a range of morphological awareness and lexical tasks. Reading ability was tested through standardized tests of reading fluency and comprehension. Results showed that L1 children outperformed L2 on every measure of morphological awareness, as well as on reading tests. Regression analyses revealed that morphological awareness contributed to a different extent to reading ability across groups. Accuracy in the morphological awareness tasks was a significant predictor of word (and non-word) reading fluency in L1 and L2 first and second graders, while only in L1 third to fifth graders, response times and accuracy to a morphological awareness task explained a unique amount of variance in reading comprehension. Our results highlight the critical role of morphological processing in reading efficiency and suggest that a training inspired by morphological awareness may improve reading skills also in bilingual students.